PERANCANGAN PLTS ATAP GEDUNG BALAI BUDAYA GIRI NATA MANDALA PUSAT PEMERINTAHAN KABUPATEN BADUNG - Andre, J.; Kumara, I N. S.; Ariastina, W. G.; Giriantari, I. A. D.; Setiawan, I N.; Sukerayasa, I W. (Jurnal SPEKTRUM, 2025)
The potential utilization of rooftop solar power plants (PLTS) in Indonesia is very large, but the realization is still relatively low, including in Bali Province. The government has set a new and renewable energy (EBT) mix target of 23% by 2025, but until 2023 it has only reached 13.1%. Government buildings have the potential to be used as pilot projects in the development of rooftop solar power plants and can become a model for the application of renewable energy in the community. This study designed a rooftop solar PV system at the Balai Budaya Giri Nata Mandala Building, Badung Regency, using 763 Trina Solar TSM-DE19R 575 Wp modules and 8 Growatt MID 50KTL3-X2 inverters. The system has a capacity of 438.7 kWp and is estimated to produce 597.7 MWh of energy per year. Simulation results show that this solar power plant can meet 28.63% of electricity demand when the building is used for events, and 34.58% when it is not used.